Development of Mathematical Reasoning Ability Test Questions on the Topic of Exponential Functions and Quadratic Functions - Kartini, Kartini; Hutapea, Nahor Murani; Rahayu, Dinda (Journal of Educational Sciences, 2025)
Mathematical Reasoning Ability (KPM) is an important ability for students to be able to think logically and draw conclusions related to mathematics. This research aims to develop KPM test questions on exponential functions and quadratic functions. This type of research is Research and Development research with a development study approach which includes preliminary stages and formative evaluation. The formative evaluation stage was adapted from Tessmer, consisting of self-evaluation, expert review, face-to-face, small groups and field tests. The test subjects for this research were students in class XI-6 of SMA Negeri 1 Pekanbaru. Based on the results of the field tests, it was obtained: (1) 15 KPM test questions on exponential functions and quadratic functions which were declared externally valid; (2) the KPM test questions have a reliability value of 0.81 which is categorized as very high; (3) KPM test questions have an average level of difficulty of 0.40 in the "medium" category; and (4) the KPM test questions have an average differentiating power value of 0.44 in the "good" category.